Experimental Choice and Disruptive Technologies - Gans, Joshua S. (Management Science, 2023)
This paper examines how a firm’s choice of the type of experiment impacts on its potential exploitation of new technological opportunities. It does so in the context of the failure of successful firms (or disruption) where the literature has informally suggested that firms undertake errors in experimental choice. It is shown that firms will generically choose experiments that minimize false positives (a high-bar) or minimize false negatives (a low-bar) rather than strike a balance between the two. This is done to better inform decisions regarding the exploitation of technological opportunities. It is shown that these choices can differ between incumbents and entrants based on their fundamentals and because of the anticipation of competition between them. This paper was accepted by David Simchi-Levi, business strategy.